The Republican People’s Party: ideology and organization between 1992 and 2007 - Önen, Levent. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2009., 2009)
This thesis analyzes the ideological and organizational character of the Cumhuriyet Halk Partisi (CHP) between 1992 and 2007. Although the CHP is put on the left on the ideological spectrum, it is actually a center right party. It is a continuation of authoritarian and nationalist one-party CHP rather than a continuation of the populist CHP of 1970s. In other words, the ideology of the CHP is in harmony with Kemalism, which was a right-wing ideology in its essence. The nationalist and statist character of this ideology was emphasized much more after 2002. In other words, there was no meaningful difference that distinguishes it from other nationalist right wing parties. The political ideology of the CHP is statist and elitist. Rather then aggregating and representing popular demands, it tries to shape political agenda through the Judiciary and the military. The main concepts that shape the political discourse and practice of the CHP are national interest, national security, nation-state, secularism and unitary state. This thesis also examine the interaction between the organizational structure and the ideology of the CHP. The CHP which was turned into a vote and office seeking party increased its emphasis on nationalism and Kemalist symbols since it could not offer an alternative program to neo-liberal paradigm. The CHP never made a serious criticism of neoliberal agenda apart from piecemeal objections in certain issues. The criticisms of the party to neo-liberalism and globalization were related not to concerns of social justice and equality, but concerns about preservation of nation state and national interest.